Microbial regulation of arsenopyrite oxidation and arsenic transformation in pyrrhotite-mediated interactions - Shuang Zhou; Yusi Qin; Zhiqi Chen; Zhenlei Cai; Yongjie Bu; Weijian Yu; Chenyang Zhang; Keyi Yang; Min Gan; Qingjun Guan (Bioresource Technology, 2027)

Diisodecyl phthalate aggravates thyroid autoimmune injury in thyroglobulin-sensitized rats via endoplasmic reticulum stress-mediated apoptosis and Th17/Treg dysregulation - Zixin Tian; Jianwei Gao; Zhenjie Lu; Keyi Chen; Wanjia Lv; Mei Ye; Yajun Wang; Yanling Sun; Xu Yang; Ping Ma; Yang Wu (Food and Chemical Toxicology, 2026)

Integrating machine learning with Raman spectroscopy for microplastic identification and classification: Method construction and application - Kaibo Jin; Yanyan Dou; Yang Li; Jingjing Lv; Xuejun Duan; Xudong Chen; Xishu Liang; Tianyu Ao; Keyi Lu; Shoukai Chen (Journal of Water Process Engineering, 2026)

The acid polysaccharides extracted from Moringa leaf improve DSS-induced ulcerative colitis by targeting intestinal microbiota metabolism - Wen Lang; Xinyun Qin; Yizhe Dou; Keyi Nong; Ruixue Cao; Tingyu Chen; Wanyan Chen; Bin Zhang; Zheng Yang; Bowen Tian; Jijun Wang; Lianbin Li; et al. (Food Research International, 2026)

Data-Driven Coastal Nutrients Estimation: Current Status, Research Gaps, and Future Developments - Sihan Ni; Jin Qi; Xiangbin Ran; Zhiqiang Liu; Sensen Wu; Minyu Wang; Keyi Yang; Chengfeng Le; Zhenhong Du (Water Research, 2026)

Searching for potential biosignatures in impact-induced hydrothermal systems on Mars - Yuchun Wu; Yang Liu; Zengqian Hou; Keyi Li; Chaolin Zhang; Yongliao Zou (Science Bulletin, 2026)

A transcriptome dataset for early phenotypic sex differentiation in the mud crab Scylla paramamosain - Haolin Yang; Zhiqiang Liu; Chunyan Ma; Wei Wang; Lingbo Ma; Keyi Ma (Frontiers in Marine Science, 2026)

Self-assembled and reversibly esterified hierarchical networks enable tough, anti-swelling and recyclable nanocomposite hydrogel - Zhengxu Jin; Ying Chen; Feihong Hu; Huizhu Wang; Qianyue Zeng; Keyi Yang; Hong Chen; Xiaoming Huang; Jing Xie; Jianshu Li (Chemical Engineering Journal, 2026)

Ruthenium supported on grain-boundary-induced oxygen-vacancy-rich CeO2 for efficient ammonia decomposition - Jinghua Liu; Wujian Zhang; Junhan Yang; Yongchao Zhao; Jian Guan; Zhenxiang Li; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Chunshan Lu; Angjian Wu; et al. (Chemical Engineering Journal, 2026)

Molecular-weight-dependent effects of humic acid on hexavalent chromium accumulation and reduction in green microalgae - Li Luo; Keyi Zhou; Mawuli Dzakpasu; Kena Zhang; Tong Yang; Wenshan Guo; Huu Hao Ngo; Xiaochang C. Wang (Journal of Hazardous Materials, 2026)

Generation of environmentally persistent free radicals in paddy soil and their impact on arsenic speciation and bioavailability: A review - Chen Chen; Nan Yang; Xiaotong Liu; Yi Zhou; Keyi Wang; Naiyi Yin; Xiaolin Cai; Yanshan Cui (Journal of Hazardous Materials, 2026)

β-Ionone inhibits A. sydowii mediated LUAD progression by inhibiting myeloid-derived suppressor cell (MDSC) expansion and activation - Xiaoping Liu; Shuhua Li; Keyi Chen; Xue Yang; Yanxia Yang; Xin Wang (Journal of Molecular Histology, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Enhanced buoy-based water quality time series imputation in coastal waters - Minyu Wang; Keyi Yang; Junyu He; Jin Qi; Yijun Chen; Haoqi Gu; Renyi Liu; Sensen Wu; Zhenhong Du (Journal of Hydrology, 2025)

A high-performance aqueous redox flow battery with long cyclic stability enabled by a novel Janus membrane self-assembled from polyelectrolytes - Quanhu Sun; Keyi Dong; Zefeng Yan; Tian Lv; Yan Tan; Jiaxin Yang; Yu Wang; Weiyang Tang; Tao Chen (Chemical Engineering Journal, 2025)

Covalency modulated by Fe-F-Fe configuration and oxygen vacancy promotes dual mechanism for oxygen evolution reaction - Bo Feng; Keyi Lv; Ziyong Zhang; Nianwen Song; Ziyang Yan; Yuchao Zhang; Yanfei Wei; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; Zunming Lu; et al. (Chemical Engineering Journal, 2025)

Spatio-seasonal variability of source contributions to water quality in a large irrigation drainage lake basin based on the entropy weighted quality index, positive matrix factorization, and isotopic tracers - Keyi Zhang; Muhan Li; Shen Qu; Yuanzhen Zhao; Limin Duan; Xu Yang; Dingyi Li; Zilong Liao; Ruihong Yu (Environmental Pollution, 2025)

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

Double special bodyguard: Selenium-enhanced loop-mediated isothermal amplification combined with CRISPR/Cas12a biosensing strategy - Keyi Long; Tiao Han; Wenxi Hu; Mei Yang; Danqun Huo; Zhen Huang; Changjun Hou (Analytica Chimica Acta, 2025)

Microbial distribution patterns and driving factors related to nitrogen cycling in karst Tiankeng soil - Xiaohui WANG; Junbo YANG; Keyi WANG; Danjuan ZENG; Ling MO; Gaozhong PU (Pedosphere, 2025)

Synergistic effects of nanoplastics and graphene oxides on microbe-driven litter decomposition in streams - Yao Wang; Keyi Wang; Junbo Yang; Mingquan Dai; Danjuan Zeng; Xiaohui Wang; Jingjing Du; Gaozhong Pu (Journal of Hazardous Materials, 2025)

Nitrogen-cycling microbial diversity and function in tiankengs at different evolutionary stages - Xiaohui Wang; Keyi Wang; Junbo Yang; Danjuan Zeng; Ling Mo; Gaozhong Pu (CATENA, 2025)

Application of a fluorescent probe exhibiting a large stokes shift after the precise detection of hydrazine in plants, foods and living cells - Yan Zhang; Yan Huang; Guiyi Yang; Haotian Xin; Keyi Li; Lei Wang; Shangcong Gu; Baosheng Ren; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2025)

Synergizing farmland reverting and energy substitution programs in Wolong through agent-based modelling and cost-efficiency analysis - Keyi Liu; Yufeng Chen; Liyan Xu; Xiao Zhang; Zilin Wang; Hailong Li; Yansheng Yang; Hong You; Dihua Li (Ecological Modelling, 2025)

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

Reconstruction of cobalt atoms in ZIF-67 and in-situ growth of carbon nanotubes at low temperature for High-Performance strain sensors - Xiao Li; Tian Lv; Keyi Dong; Jiaxin Yang; Weiyang Tang; Zilin Chen; Yu Duan; Quanhu Sun; Dongmei Zhai; Tao Chen (Chemical Engineering Journal, 2025)

Design of F doped sulfide bifunctional catalyst and investigation on the mechanism transformation of oxygen evolution reaction - Nianwen Song; Keyi Lv; Bo Feng; Ziyong Zhang; Xiangwen Tan; Yanfei Wei; Ziyang Yan; Yuchao Zhang; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; et al. (Chemical Engineering Journal, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Chronosequence changes in soil microbes under Populus simonii × P. nigra stands: Implications for soil health restoration in Mollisols - Jia Yang; Qinghua Liu; Keyi Liu; Shunzhong Wang; Huiyan Gu (Applied Soil Ecology, 2025)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Identification and characterization of autoallododecaploid barnyard grass (Echinochloa crus-galli L.) induced by in vitro colchicine treatment - Keyi Liu; Xiaoling Zhou; Wei Wang; Xiaoxiao Wu; Ziwei Zhao; Xiaolu Yang; Ziyi Feng; Pincang Lv; Jie Wang; Wangwen Zhu; Xianhua Zhang; Yuchi He; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Realizing reasonable redistribution of platform capacity through valence structure optimization for low strain Na3MnZr(PO4)3 cathode material - Mengting Deng; Yulei Sui; Kexin Rao; Yian Wang; Wenbin Fei; Keyi Sun; Zonglin Yang; Xiaoping Zhang; Ling Wu (Chemical Engineering Journal, 2024)

Multi-isotopes (δD, δ18Owater, 87Sr/86Sr, δ34S and δ18Osulfate) as indicators for groundwater salinization genesis and evolution of a large agricultural drainage lake basin in Inner Mongolia, Northwest China - Shen Qu; Yuanzhen Zhao; Keyi Zhang; Juliang Wang; Muhan Li; Xu Yang; Xiaohui Ren; Yanling Hao; Ruihong Yu (Science of The Total Environment, 2024)

The mechanistic insights and therapeutic implications of sheepskin collagen peptide as a novel anti-photoaging agent - Baifeng Fu; Keyi Zhou; Hui Yao; Ximing Yang; Xiaoyu Ma; Qi Yang; Shuzhen Cheng; Ming Du (Food Bioscience, 2024)

Near-infrared and multifunctional fluorescent probe enabled by cyanopyridine cyanine dye for bisulfite recognition and biological imaging - Shangcong Gu; Yan Huang; Xinxin Li; Haotian Xin; Haoran Mu; Yan Zhang; Keyi Li; Guiyi Yang; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2024)

Corrigendum to “Microcystin-LR improves anti-tumor efficacy of oxaliplatin through induction of M1 macrophage polarization” [Toxicon 2024 May 28;243(0):107723] - Keyi Li; Minzhu Yang; Yuxin Dai; Jinyan Huang; Peng Zhu; Qiuzhen Liu (Toxicon, 2024)

Rational design of bilayer heterogeneous poly(ionic liquid)s electrolytes for high-performance flexible supercapacitors with ultraslow self-discharge rate - Keyi Dong; Weiyang Tang; Quanhu Sun; Zilin Chen; Xiao Li; Dongmei Zhai; Zefeng Yan; Jiaxin Yang; Tian Lv; Tao Chen (Chemical Engineering Journal, 2024)

Interfacial solar evaporation driven Cd removal from contaminated sediments - Keyi Liu; Pan Wu; Yang Ye; Jiashu Jiang; Yuhao Guo; Yuejianshu Li; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2024)

Microcystin-LR improves anti-tumor efficacy of oxaliplatin through induction of M1 macrophage polarization - Keyi Li; Minzhu Yang; Yuxin Dai; Jinyan Huang; Peng Zhu; Liu Qiuzhen (Toxicon, 2024)

Carboniferous integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Keyi Hu; Xiangdong Wang; Wenqi Wang; Yingfan Song; Xunyan Ye; Lu Li; Yukun Shi; Sunrong Yang; Ying Li (Science China Earth Sciences, 2024)

Detection and treatment of mono and polycyclic aromatic hydrocarbon pollutants in aqueous environments based on electrochemical technology: recent advances - Guangfei Qu; Guojun Liu; Chenyang Zhao; Zheng Yuan; Yixin Yang; Keyi Xiang (Environmental Science and Pollution Research, 2024)

Proposal and application of onshore lattice wind turbine support structure and integrated multi-scale fatigue assessment method - Chuannan Xiong; Kaoshan Dai; Yuxiao Luo; Zufei Yang; Keyi Qiu; Hang du; Xiao Tang (Engineering Structures, 2024)

Microplastics sequestered in the soil affect the turnover and stability of soil aggregates: A review - Tianhang Ju; Kai Yang; Lei Chang; Keyi Zhang; Xingyi Wang; Jialin Zhang; Bo Xu; Yuefen Li (Science of The Total Environment, 2023)

Large-scale surface water-groundwater origins and connectivity in the Ordos Basin, China: Insight from hydrogen and oxygen isotopes - Shen Qu; Chenyu Wang; Nuan Yang; Limin Duan; Ruihong Yu; Keyi Zhang; Muhan Li; Pengfei Sun (Environmental Research, 2023)

Cotton-based bionic tree-shaped photothermal evaporator for extraction of heavy metals from river sediment - Keyi Liu; Yuejianshu Li; Pan Wu; Yuhao Guo; Yang Ye; Jiashu Jiang; Jiankai Hu; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Physical activity can influence the relationship between ethylene oxide and risk of kidney stones: A cross-sectional study from the NHANES 2013–2016 - Hua Jiang; Keyi Wang; Heng Zhang; Bin Yang; Weipu Mao; Ming Chen; Shuigen Zhou (Environmental Science and Pollution Research, 2023)

Enabling efficiency-driven and low-impact water management from robust decision making: A risk- and robustness-based multi-objective decision support model - Yang Zhou; Bing Li; Jingcheng Han; Guojian He; Keyi Wang; Chunjiang An; Yuefei Huang (Journal of Cleaner Production, 2023)

Kynurenic acid mediates bacteria-algae consortium in resisting environmental cadmium toxicity - Xiaoli Qi; Keyi Fu; Mingyuan Yue; Na Shou; Xuefeng Yuan; Xi Chen; Chunyu He; Yunfeng Yang; Zunji Shi (Journal of Hazardous Materials, 2023)

A synthesis of Carboniferous stratigraphy in Xinjiang, Northwest China with emphasis on regional and global correlations - Yong Tang; Xunyan Ye; Xiatian Wang; Xing Huang; Zhangshuai Hou; Keyi Hu; Sunrong Yang; Ying Li; Feifei Zhang; Shuzhong Shen; Xiangdong Wang (Journal of Asian Earth Sciences, 2023)

Easy regulation of chitosan-based hydrogel microstructure with citric acid as an efficient buffer - Keyi Li; Xueting Yang; Xin Dong; Hongyan Cao; Shujuan Zhuang; Xiangling Gu (Carbohydrate Polymers, 2023)

A novel defined risk signature of endoplasmic reticulum stress-related genes for predicting the prognosis and immune infiltration status of ovarian cancer - Jiahang Mo; Shunyi Ruan; Baicai Yang; Yunfeng Jin; Keyi Liu; Xukai Luo; Hua Jiang (Journal of Zhejiang University-SCIENCE B, 2023)

Effect of Dissipation on the Moonpool-Javelin Wave Energy Converter - Dan Yu; Keyi Wang; Yeqing Jin; Fankai Kong; Hailong Chen; Can Yang (Journal of Marine Science and Engineering, 2021)
In this work, the hydrodynamic performance of a novel wave energy converter (WEC) configuration which combines a moonpool platform and a javelin floating buoy, called the moonpool–javelin wave energy converter (MJWEC), was studied by semianalytical, computational fluid dynamics (CFD), and experimental methods. The viscous term is added to the potential flow solver to obtain the hydrodynamic coefficients. The wave force, the added mass, the radiation damping, the wave capture, and the energy efficiency of the configuration were assessed, in the frequency and time domains, by a semianalytical method. The CFD method results and the semianalytical results were compared for the time domain by introducing nonlinear power take-off (PTO) damping; additionally, the viscous dissipation coefficients under potential flow could be confirmed. Finally, a 1:10 scale model was physically tested to validate the numerical model and further prove the feasibility of the proposed system.

Cloning and functional characterization of PjCAO gene involved in chlorophyll b biosynthesis in Pseudosasa japonica cv. Akebonosuji - Keyi Jiang; Mingbing Zhou; Haiyun Yang; Wei Fang (Trees, 2016)